2022
DOI: 10.1002/adfm.202208074
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose‐Reinforced Programmable and Stretch‐Healable Actuators for Smart Packaging

Abstract: Biomimetic actuators are promising candidates for smart soft robotics. The applications of state‐of‐the‐art actuators require the combination of programmable stimuli‐responsiveness, excellent robustness, and efficient self‐healing ability in a wide‐range of working conditions. However, these properties may be mutually exclusive. Inspired by biological tissues, two kinds of polyelectrolytes including polyvinyl alcohol (PVA) and polystyrene sulfonate (PSS) are exploited as the fillers of cellulose nanofibrils (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The tensile strengths of PVA-MIPA10, PVA-MIPA10, and PVA-MIPA20 were 31.31 ± 0.50, 42.01 ± 2.77, and 29.56 ± 1.76 MPa. The addition of MICA and MIPA can significantly improve the composite film's mechanical strength, 62 primarily due to strong intermolecular forces generated between MICA, MIPA, and PVA molecules to form a densely cross-linked network structure. Furthermore, the elongation at break of composite films with the addition of MICA and MIPA was significantly improved compared to that of pure PVA and increased with increasing MICA and MIPA contents.…”
Section: Leachability and Morphological Analysis Of Cellulose-based C...mentioning
confidence: 99%
“…The tensile strengths of PVA-MIPA10, PVA-MIPA10, and PVA-MIPA20 were 31.31 ± 0.50, 42.01 ± 2.77, and 29.56 ± 1.76 MPa. The addition of MICA and MIPA can significantly improve the composite film's mechanical strength, 62 primarily due to strong intermolecular forces generated between MICA, MIPA, and PVA molecules to form a densely cross-linked network structure. Furthermore, the elongation at break of composite films with the addition of MICA and MIPA was significantly improved compared to that of pure PVA and increased with increasing MICA and MIPA contents.…”
Section: Leachability and Morphological Analysis Of Cellulose-based C...mentioning
confidence: 99%
“…It includes not only natural materials such as cotton, 88 cellulose, 89 rubber, 90 starch, 91 and protein, 92 but also synthetic materials such as poly(ethylene glycol), 93 Nafion, 94 polyethylene- co -acrylic acid, 95 polyamide, 96 and polyvinyl alcohol. 97 In addition to these organic materials, inorganic materials such as graphene oxide (GO), 98 carbon nanotubes, 99 montmorillonite clay, 100 MXene, 101 carbon nitride, 102 silica, 103 titanium oxide, 104 and MOFs 105 can also achieve hygroscopic swelling properties after reasonable design, and the hygroscopic swelling behavior of these materials is highly dependent on their hydrophilicity and water absorption.…”
Section: Moisture-responsive Actuatorsmentioning
confidence: 99%
“…For instance, Chen et al demonstrated a toughening and self-healing actuator composed of CNFs, polyvinyl alcohol (PVA) and polystyrene sulfonate (PSS). 51 The flexible CNF/PVA and rigid PVA/PSS networks contributed to the high toughness of the actuator due to the effective energy dissipation during stretching process. Self-healing properties of the actuators were achieved by soaking-evaporation treatment to repair intramolecular hydrogen bonds broken by an external force.…”
Section: Isotropic Actuators In Response To Non-uniform Stimulimentioning
confidence: 99%